Pengaruh Penyuluhan Kesehatan Bahaya Rokok Terhadap Pengetahuan Remaja Masjid Raya KH. Hasyim Asy'ari Tahun 2021 - Novia Kusumawati, (2021)
The dangers of smoking can cause various chronic diseases and even death, but this does not affect the percentage of smokers. In 2019, West Jakarta became the area in DKI Jakarta that had the highest number of smokers aged > 15 years, which was 29.1% or an average of 73 cigarettes per week. The high number of adolescent smokers is due to the lack of knowledge of adolescents about the dangers of smoking, for this reason it is necessary to conduct counseling about the dangers of smoking in adolescents. This study aims to determine the effect of counseling on the dangers of smoking on the knowledge of teenagers at Masjid Raya KH. Hasyim Asy'ari. This study used a Pre Experimental One Group Pre-Test and Post-Test which was conducted from March to June 2021. The population of this study was the Youth of Masjid Raya KH. Hasyim Asy'ari with a total sample of 80 teenagers with a total sampling technique. The instrument used to measure adolescent knowledge is in the form of a questionnaire distributed via google form. This study uses the Wilcoxon test analysis. The results showed that there was a difference in adolescent knowledge before and after counseling on the dangers of smoking, adolescents who had good knowledge increased to 56.3%. The conclusion of this study is that there is an effect of counseling on the dangers of smoking on adolescent knowledge with a p value of 0.000. After being given counseling, it is hoped that teenagers will have the motivation to stop smoking and share information about the dangers of smoking to others.